2022
DOI: 10.1097/cce.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Community ICUs Participating in a Critical Care Randomized Trial: A Comparison of Patient Characteristics and Trial Metrics

Abstract: OBJECTIVES:Clinical research in Canada is conducted primarily in "academic" hospitals, whereas most clinical care is provided in "community" hospitals. The objective of this nested observational study was to compare patient characteristics, outcomes, process-of-care variables, and trial metrics for patients enrolled in a large randomized controlled trial who were admitted to academic and community hospitals in Canada. DESIGN:We conducted a preplanned observational study nested within the Probiotics: Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Partly, this is because the scope of the papers included has increased. There are many more studies where all the clinicians or organisations compared are engaged in research but to varying extents and/or with different levels of resources, for example within a trial [28, 50,59,73,93,103,107], or within a network [23,33,49,51,66,68,69,85,95]. The inclusion of papers about differences within trials, and the emergence of the importance of the "dose effect", have implications for both a) how the issue of research engagement is analysed, and b) how far efforts to enhance research engagement should be concentrated or spread widely across a system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partly, this is because the scope of the papers included has increased. There are many more studies where all the clinicians or organisations compared are engaged in research but to varying extents and/or with different levels of resources, for example within a trial [28, 50,59,73,93,103,107], or within a network [23,33,49,51,66,68,69,85,95]. The inclusion of papers about differences within trials, and the emergence of the importance of the "dose effect", have implications for both a) how the issue of research engagement is analysed, and b) how far efforts to enhance research engagement should be concentrated or spread widely across a system.…”
Section: Discussionmentioning
confidence: 99%
“…In the with the assumption that by participating as equals in the research process, community physicians would be more likely to accept and implement the results in their practices with non-protocol patients" (p.336) [37]. Similar moves to encourage wider participation in clinical trials have recently been made in Canada in the nested study described above [103]. And a recent analysis showing higher levels of research activity within the English healthcare system are associated with lower mortality, notes that although the NIHR CRN was established to promote research participation across England, there is still some way to go to ensure greater geographical equity [69].…”
Section: Health Equitymentioning
confidence: 93%
See 1 more Smart Citation
“…Institutions can explore ways to increase enrollment success such as video-based or e-Consent strategies [3]. In Canada, the majority of ICU care is provided by community hospitals, which have limited participation in clinical trials or other research [6,7]. Given that community sites disproportionately serve racialized and socio-economically deprived Canadians, their involvement in research is critical to improve research participant diversity in Canadian critical care trials [6].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the majority of ICU care is provided by community hospitals, which have limited participation in clinical trials or other research [6,7]. Given that community sites disproportionately serve racialized and socio-economically deprived Canadians, their involvement in research is critical to improve research participant diversity in Canadian critical care trials [6]. A recent Canadian study demonstrated that community ICUs can conduct research with comparable recruitment rates, consent rates, and protocol adherence when compared to academic ICUs [6].…”
Section: Discussionmentioning
confidence: 99%